Survival of individuals with cerebral palsy in Victoria, Australia: A longitudinal cohort study spanning four decades. (26th September 2022) - Hinwood, Gina L.; Loftus, Hayley; Shepherd, Daisy A.; Guzys, Angela; Reddihough, Dinah S.; Reid, Susan M.
Abstract: Aim: To provide an updated description of the rates, trends, and predictors of mortality of individuals with cerebral palsy (CP), born in the Australian state of Victoria between 1970 and 2012. Method: Data were extracted for 4807 individuals (2091 females; 2716 males). The probability of survival to 30th June 2017 was calculated using the Kaplan–Meier method. Mortality rates were calculated per 1000 person‐years using age strata and compared with population mortality rates to produce mortality ratios. Cox proportional hazards regression was used to calculate hazard ratios for selected demographic and clinical characteristics and to estimate the effect of birth epoch on 15‐year survival. Results: There were 666 recorded deaths. Compared to the general population, mortality was higher for all persons with CP and highest for children aged 1 to 15 years (45–62 times). We observed 35% improvement in the probability of survival to 15 years for births in the 2000s relative to the 1970s (hazard ratio 0.65, 95% confidence interval [CI] 0.49, 0.86), but only 4% improvement for the subgroup with complex CP (hazard ratio 0.96, 95% CI 0.69, 1.33). Interpretation: The observed improvements in survival for those born in the 2000s is likely related predominantly to a proportional reduction in complex CP within the cohort. What this paper adds: Length of survival improved for Australians with cerebral palsy (CP) born this millennium. Improved survival was mainly because of a proportional reduction in complex CP. A small improvement in length of survival was seen for children with complex CP. What this paper adds: Length of survival improved for Australians with cerebral palsy (CP) born this millennium. Improved survival was mainly because of a proportional reduction in complex CP. A small improvement in length of survival was seen for children with complex CP. Improvements in survival in our most recent birth cohorts were predominantly related to changes in severity profiles of the Victorian population with cerebral palsy (CP). Although we observed 90% survival to 18 years, it was reduced to 66% for persons with complex CP. This is consistent with the increased risk of mortality in association with poor gross motor function, bilateral CP (quadriplegia), deafness, epilepsy, and lack of speech. Mortality was highest for children under 15 years in comparison to rates for the general population.